SOME FEATURES OF HUMAN LIPID AND CARBOHYDRATE METABOLISM IN THE NORTH - Ye. V. Sevostyanova (Бюллетень сибирской медицины, 2013)
In the review the current understanding of some clinically and pathogenetically meaningful features of the lipid and carbohydrate metabolism in the indigenous and migrant population of the North and equivalent areas of Siberia are stated. Physiological and pathophysiological importance of the changes in human metabolism in the North are discussed in connection with the processes of adaptation and disadaptation to extreme climatic and geographical factors.